2022
DOI: 10.3389/fenvs.2022.988921
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors of CO2 emissions and the adoption of eco-innovation across G-7 economies: A novel hybrid mathematical and statistical approach

Abstract: The present study empirically analyzes the role of eco-innovation in plummeting carbon dioxide (CO2) emissions in conjunction with renewable energy usage, foreign direct investment, and trade openness for the states in G-7 from 1990 to 2019 in a mathematical and statistical context. Under the dynamical framework, the estimates of mathematical grey relational analyses indicate that eco-innovation holds a stronger degree of association with CO2 emissions. Further, the estimates demonstrate that, compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The authors emphasized the role that urbanization played in lowering emission levels and mentioned that more comprehensive policies were needed to tackle the environmental degradation of urbanization. Rehman et al [64] examined G7 countries from 1990 to 2019, and FDI and trade openness largely increased CO 2 emissions in Canada and Germany, while that effect was the opposite in the US and the UK. Shah et al [65] showed that there was a dynamic association between oil prices and emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors emphasized the role that urbanization played in lowering emission levels and mentioned that more comprehensive policies were needed to tackle the environmental degradation of urbanization. Rehman et al [64] examined G7 countries from 1990 to 2019, and FDI and trade openness largely increased CO 2 emissions in Canada and Germany, while that effect was the opposite in the US and the UK. Shah et al [65] showed that there was a dynamic association between oil prices and emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The future entails actively promoting the use of urban greening projects at national, regional, and local levels through sustainable development programs (Chen et al, 2023;Evans & Hardman, 2023). The anticipated long-term outcomes of such a management strategy encompass the enhancement of social and environmental microclimates in cities, increased economic efficiency of projects, and an overall improvement in the living environment (Kruize et al, 2020;Rehman et al, 2022;Grigoletto et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Akram et al [ 30 ] noted that environmental innovations have a negative and significant impact on CDEs in both the short and long term, thereby contributing to the achievement of carbon neutrality within G7 countries. Rehman et al [ 49 ] noted that trade openness and foreign direct investment increased CDEs in Germany and Canada, while reducing them in the UK and US.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%